Strategies of the Russian Oil and Gas Companies at the Era of Energy Transition - M. I. Riabova (Vestnik MGIMO-Universiteta)
Exacerbating climatic change accelerates the formation of ESG national regulatory approaches and the development of non-financial reporting, stimulating new green financing mechanisms both abroad and in Russia. Russian oil and gas companies, particularly Lukoil, Rosneft, and Tatneft, demonstrate the strengthening of environmental and social components in their reports, administration restructures, and improved corporate regulatory documentation concerning the principles of sustainable development. Due to the national features of regulatory and market approaches, European companies are more ambitious regarding the pace of their energy transition and updating the climatic agenda at all operating levels.The article compares the strategies of European energy companies (Shell, Eni, Totlenergies) and Russian energy companies (Lukoil, Rosneft, and Tatneft) in sustainable development and energy transition. The case selection is based on positive financial indicators and companies’ progress in sustainability rankings, such as ACRA, WFF Russia, CDP, and TPI. In conclusion, the article identifies the following priority corporate strategies: digitalization as a way of reducing emissions; an increase in the share of the gas business; development of renewable energy sources; optimization of the internal structure; adding ESG indicators to the leadership’s KPI; adding ESG indicators to requirements for contractors.